Seasonality and Dynamics of Gastrointestinal Helminths in Grazing Horses - De Lima Saes, Isabela [UNESP]; Gonçalves, Juliana Alencar [UNESP]; Do Carmo, Tábata Alves [UNESP]; Mena, Mateus Oliveira [UNESP]; De Almeida Cipriano, Isabela [UNESP]; De Favare, Giordani Mascoli [UNESP]; Bello, Hornblenda Joaquina Silva [UNESP]; Guelpa, Gabriel Jabismar [UNESP]; De Soutello, Ricardo Velludo Gomes [UNESP] (De Gruyter, 2022)
The prevalence of helminths in horses may vary, depending on climatic factors and host susceptibility. The objective of this study was to evaluate the seasonal dynamics of helminth infection in grazing horses, from October 2015 to September 2016. In total, 104 crossbred horses of different age groups, males and females in a single herd, participated in this study. Individual fecal samples were collected every 28 days for counting of eggs per gram of feces (EPG) and fecal cultures. The horses were evaluated individually for weight, body condition score (BCS) and clinical status. Climatic information relating to the farm was also collected. The categories most affected by helminths were foals and senior horses, with EPG averages of 1271.9 and 1186.5, respectively. The EPG averages for all animal categories together, in the four seasons were: 1042.1 spring; 1508.9 summer; 817.8 autumn; and 571.1 winter. Through the body condition evaluation, it was seen that senior animals presented the lowest BCS in all seasons. It was concluded that the season in which these animals were most affected by helminth infections was the summer and that the most susceptible categories were foals and senior horses.
Keywords: equines; nematodes; prevalence; susceptibility